Depressive symptoms are associated with poor glycemic control among women with type 2 diabetes mellitus - Góis, Carlos (2018)
OBJECTIVE: In patients with type 2 diabetes mellitus, depressive symptoms may be associated with metabolic deterioration. The impact of sex on this association is unclear. The aim of this study is to analyze the relationship between depression and metabolic control by sex. The data presented is the side product of the clinical investigation by Rui Duarte, MD, Treatment Response in Type 2 Diabetes Patients with Major Depression from 2007. RESULTS: A sample of 628 outpatients with type 2 diabetes mellitus was taken from a specialized diabetes outpatient clinic. In a univariate analysis: women's glycohemoglobin mean levels were 8.99% whereas men's were 8.41% and the difference was statistically significant. The proportion of women (34.3%) with pathological levels of depression (Hospital Anxiety Depression Scale score ≥ 8) was significantly higher than men's (15.2%). A linear regression analysis performed by sex and controlling for demographic, clinical and psychological variables, showed poorer metabolic control in women with depressive symptoms. No association was observed in men. These results support depression as a predictor for poor metabolic control in women and the need for detecting depressive symptoms when glycemic levels deteriorate.